The siege : a novel - Pérez-Reverte, Arturo (Random House, 2014)
"Cádiz, 1811. The Spanish port city has been surrounded by Napoleon's army for a year. Their backs to the sea, its residents endure routine bombardments and live in constant fear of a French invasion. And now the bodies of random women have begun to turn up throughout the city, victims of a shadowy killer. Police Comisario Rogelio Tizón has been assigned the case. Known for his razor-sharp investigation skills--as well as his brutal interrogation methods--Tizón has seen everything. Or so he thought"--Amazon.com.